Prevalence and reasons for Juul use among college students - Ickes, Melinda (J Am Coll Health, 2019)
OBJECTIVE: Examine Juul use patterns, sociodemographic and personal factors associated with Juul use, and reasons for Juul initiation and current use, among college students. PARTICIPANTS: Convenience sample of 371 undergraduates at a large university in the southeast; recruited April 2018. METHODS: Cross-sectional design using an online survey. Logistic regression identified the personal risk factors for current use. RESULTS: Over 80% of participants recognized Juul; 36% reported ever use and 21% past 30-day use. Significant risk factors for current Juul use were: male, White/non-Hispanic, lower undergraduate, and current cigarette smoker. Current Juul users chose ease of use and lack of a bad smell as reasons for use. Ever Juul users most commonly endorsed curiosity and use by friends as reasons for trying Juul. Conclusions: Given the propensity for nicotine addiction among youth and young adults, rates of Juul use are alarming and warrant immediate intervention.